2022
DOI: 10.1029/2022sw003130
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of SuperDARN Backscatter Modes Using Machine Learning Guided by Ray‐Tracing

Abstract: The Super Dual Auroral Radar Network (SuperDARN) is a network of High Frequency (HF) radars that are typically used for monitoring plasma convection in the Earth's ionosphere. A majority of SuperDARN backscatter can broadly be divided into three categories: (a) ionospheric scatter due to reflections from plasma irregularities in the E and F regions of the ionosphere, (b) ground scatter caused by reflections from the ground/sea surface following reflection in the ionosphere, and (c) backscatter from meteor trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…It is possible that some of the non‐grainy near range BKS observations might be direct backscatter from Es layers. Our previous study (Kunduri et al., 2022) showed that the E‐region backscatter and meteor scatter can occur in the same ranges and such backscatter increases during summer, when Es are most frequently observed. Identifying the source of the non‐grainy echoes is beyond the scope of our current analysis, but will be pursued during future experimental campaigns between the Millstone Hill ISR and SuperDARN.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that some of the non‐grainy near range BKS observations might be direct backscatter from Es layers. Our previous study (Kunduri et al., 2022) showed that the E‐region backscatter and meteor scatter can occur in the same ranges and such backscatter increases during summer, when Es are most frequently observed. Identifying the source of the non‐grainy echoes is beyond the scope of our current analysis, but will be pursued during future experimental campaigns between the Millstone Hill ISR and SuperDARN.…”
Section: Discussionmentioning
confidence: 91%
“…This is particularly an issue when a radar's observational geometry is perpendicular to the ionospheric flow direction, and also at mid-latitudes where the velocity of quiet-time ionospheric irregularities can be as low as a few tens of meters per second (Maimaiti et al, 2018;Ribeiro et al, 2012;Wang et al, 2022). Several techniques for improved classification of backscatter sources have been developed in recent years (e.g., Bland et al, 2014;Burrell et al, 2015;Kong et al, 2024;Kunduri et al, 2022;Ribeiro et al, 2011), which could be used to pre-process input data before applying the multifrequency calibration technique to obtain improved t diff estimates.…”
Section: Discussionmentioning
confidence: 99%
“…DBSCAN has previously been employed for SuperDARN backscatter characterisation as part of Kunduri et al's (2022) machine learning framework with success. Echoes with elevations below and above 40° are clustered in separate instances, as this provides separation in cases where backscatter is observed across most range gates that may otherwise be incorrectly grouped.…”
Section: Echo Cluster Filteringmentioning
confidence: 99%